FEATURES OF THE SUBSONIC WIND TUNNEL EXPERIMENT WITH ROTATING MODELS OF AIRCRAFT - A. G. Golubev; A. A. Michkin; E. G. Stolyarova (Научный вестник МГТУ ГА, 2016)
Paper contains description of the construction of aircraft model for aerodynamic experiment in subsonic wind-tunnel, during it rotation. The technique of the experiment, and features associated with rotation were mentioned. Provided the results of measuring Magnus force and it comparing with analytical methodology.